The Braconid and Ichneumonid parasitoid wasps : biology, systematics, evolution and ecology - Quicke, Donald L. J. (Wiley Blackwell, 2014)
The Ichneumonoidea is a vast and important superfamily of parasitic wasps, with some 60,000 described species and estimated numbers far higher, especially for small-bodied tropical taxa. The superfamily comprises two cosmopolitan families - Braconidae and Ichneumonidae - that have largely attracted separate groups of researchers, and this, to a considerable extent, has meant that understanding of their adaptive features has often been considered in isolation. This book considers both families, highlighting similarities and differences in their adaptations.